2018
DOI: 10.4314/ijbcs.v12i2.21
|View full text |Cite
|
Sign up to set email alerts
|

Antinutriments et propriétés nutritionnelles in vivo de Cochlospermum tinctorium A. Rich. (Bixaceae) chez les jeunes rats (Rattus norvegicus L.)

Abstract: Cochlospermum tinctorium A. Rich. (Bixaceaee) est une plante répandue dans la bande sahélosoudanienne africaine. Sa racine tubéreuse est utilisée soit comme aliment de soudure et soit comme un organe végétal hépatoprotecteur. Cette racine a été prélevée à Mindaoré/Fianga (Tchad), réduite en poudre et soumise à des analyses chimiques des antinutriments selon des méthodes bien documentées avant d'être testée sur cinq groupes de rats albinos (Rattus norvegicus L). A la fin de l'expérimentation, des analyses bioch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…ese results are not consistent with those of Ndouyang et al who found that the root powder of C. tinctorium increases the serum lipid levels in rats and thereby leading to a rise in the atherogenic index. [10] Attacks by free radicals cause acute and chronic liver toxicity, leading to necrosis, fibrosis, steatosis, and cirrhosis. [35] e metabolism of CCl4 by liver cells leads to the formation of free radicals which reduce the levels of antioxidant enzymes, increase malondialdehyde, and cause oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ese results are not consistent with those of Ndouyang et al who found that the root powder of C. tinctorium increases the serum lipid levels in rats and thereby leading to a rise in the atherogenic index. [10] Attacks by free radicals cause acute and chronic liver toxicity, leading to necrosis, fibrosis, steatosis, and cirrhosis. [35] e metabolism of CCl4 by liver cells leads to the formation of free radicals which reduce the levels of antioxidant enzymes, increase malondialdehyde, and cause oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…[9] Among these plants, we find Coclospermum tinctorium (Cochlospermaceae) which is a well-known plant in phytotherapy. [10][11][12][13] e rhizome of C. tinctorium is used against fever, hepatitis, inflammation, abdominal pain, helminth infections, and bilharziasis. [11] In Senegal and Niger, C. tinctorium is used to treat liver disease, but also rickets, colic, helminthiasis, and beriberi.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The plant materials, the fresh roots of Cochlospermum tinctorium were collected in the village of Mindaore (local name of the plant in Tupuri language: 'Belyewn'), at the Eastern of the region of Mayo-Kebbi in Chad. The sample was taken to the Laboratory of Biophysics, Food Biochemistry and Nutrition of ENSAI/ University of Ngaoundere Cameroon for unit operations by using separately two different processing as reported by Ndouyang et al (2018). The cuticle was discarded, and the first operation being a traditional household process consisted of reducing the inner matrix of the root in slices and of dividing the skin of the same root in small pieces; the second involved soaking processing of a part of the root inner matrix.…”
Section: Plant Materials and Dryingmentioning
confidence: 99%
“…According to many authors, the root of Cochlospermum tinctorium (also called rhizome) is used in the prevention or treatment of malaria (Benoit et al, 1995;Guiguemde et al, 2000;Zederkopff-Ballin et al, 2002;Ahmadu et al, 2014), bacterial diseases (Ouattara et al, 2007;Tidjani et al, 2009;Magaji et al, 2010), hepatic affections such as jaundice, chronic hepatitis B (Etuk et al, 2009a;Akinloye et al, 2011;Akinloye et al, 2012;Musa et al, 2012). It is also used in controlling physiological disorders such as hyperglycemia (Ndouyang et al, 2018), convulsion (Maiha et al, 2009), inflammation and pain (Nergard et al, 2005;. In addition, the root of plants of the genus Cochlospermum used against viruses was also reported (Solon et al, 2012;Musa et al, 2012).…”
Section: Introductionmentioning
confidence: 99%